2008
DOI: 10.1002/j.1556-6978.2008.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Perspectives in Supervision: Using a Peer Consultation Model to Enhance Supervisor Development

Abstract: Research and literature in the profession of counselor supervision primarily focus on the development of the trainee and what supervision and supervisors can do to help foster that development. Considerably less attention has been paid to the developmental path of the supervisor or how specific training or experiences in supervision can be used in intentional ways to help influence the development of the supervisor. This article reviews what is known about supervisor development and discusses a specific interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Granello, Kindsvatter, Granello, Underfer‐Babalis, and Hartwig‐Moorhead () recommended that process groups should meet in smaller reflection and case study teams to form stronger bonds for support within their small group. This model suggests that the group meet several times per year, either via videoconferencing or in person, to provide new perspectives and legal consultation and to enhance cognitive complexity in supervisors.…”
Section: Methods Of Preparing Site Supervisorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Granello, Kindsvatter, Granello, Underfer‐Babalis, and Hartwig‐Moorhead () recommended that process groups should meet in smaller reflection and case study teams to form stronger bonds for support within their small group. This model suggests that the group meet several times per year, either via videoconferencing or in person, to provide new perspectives and legal consultation and to enhance cognitive complexity in supervisors.…”
Section: Methods Of Preparing Site Supervisorsmentioning
confidence: 99%
“…Group supervision training provides resources and opportunities for peer consultation regarding issues that a supervisor has experienced in supervi-sion and can serve as a preventative measure, as opposed to trying to resolve a problem after it has already occurred (DiMino & Risler, 2012). Granello, Kindsvatter, Granello, Underfer-Babalis, and Hartwig-Moorhead (2008) recommended that process groups should meet in smaller reflection and case study teams to form stronger bonds for support within their small group. This model suggests that the group meet several times per year, either via videoconferencing or in person, to provide new perspectives and legal consultation and to enhance cognitive complexity in supervisors.…”
Section: Group Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for specialized training for clinical supervisors has become apparent (Granello, Kindsvatter, Granello, Underfer‐Babalis, & Moorhead, 2008). Baker, Exum, and Tyler (2002) suggested that longevity as a counselor can no longer serve as a single indicator of adequate supervisor preparation.…”
Section: Clinical Supervisionmentioning
confidence: 99%
“…First, there is research that addresses the importance of clinical supervision on the overall development of the counselor (Baird, 2011; Getz, 2001; Granello et al, 2008). Second, there is research that emphasizes the unique knowledge base and skills associated with clinical supervision (Bernard, 1979, 1981; Granello et al, 2008; Kaiser & Kuechler, 2008; McMahon & Simons, 2004). There appears to be a gap in the research that examines the degree to which the special knowledge base and skills associated with clinical supervision and represented in the literature are present in actual clinical supervision activities.…”
Section: Clinical Supervision In the Substance Abuse Treatment Fieldmentioning
confidence: 99%